The Foreshore and Seabed Act: Five years on, where to from here - Whare, Tracey (Māori and the environment: kaitiaki, 2010)
Keywords: citizenship; environment; environmental policy; kaitiakitanga; print only; social life and customs; taiao; water management

Mana Maori: questions of authority on the East Coast during the nineteenth century - Smit, Grace (Thesis MA--History--University of Auckland., 1997)
Keywords: leadership; new zealand wars; ngāti kahungunu; ngāti rākaipaaka; print only; rangatiratanga; wairoa

Cultural and intellectual property rights: a series of readers examining critical issues in contemporary Māori society - Pihama, Leonie; Smith, Cherryl Waerea-i-te-Rangi (Economics, politics & colonisation ; v. 2, 1997)
Keywords: civil Rights; colonisation; intellectual property; print only; treaty claims

The greatest good for the greatest number?: Rangatiratanga and the reform of local government 1987-1990 - Crengle, Diane (1993)
Keywords: crown law; local government; not sure if maori; print only; resource management act 1991; thesis; tiriti o waitangi/treaty of waitangi

He Koha Kei Roto: He Utu Kei Waho - Kohere, Rarawa D. (ResearchSpace@Auckland, 1992)
This research focuses on the period 1830 to 1992 and is a descriptive account as well as an analysis of Ngati Piritai interaction with Pakeha over that time. This thesis details a history of struggle for control over the legitimacy and validity of the Ngati Piritai cultural imperative within a social context characterised by dominant Pakeha and subordinate Maori relations. It draws upon a range of sources and brings together the experiences of an historical sampling of Ngati Piritai whanau members covering a six generation framework of Maori - Pakeha interactions. An examination of Pakeha efforts to establish hegemonies of colonisation over Maori through educational indices is made using the critical frameworks of educational theorists such as Giroux, Bernstein, Bourdieu, Gibson, Apple, Marcuse, Shuker, and Dale. Conversely Maori efforts to maintain their cultural identity and their culture, 'per se', through counter hegemonic processes such as the control over educational frameworks are also examined. For example the control over knowledge and how such control relates to enhancing social mobility, attaining outcomes of social justice, and delivering more equitable educational outcomes are also explored. A major argument is that Maori - Pakeha inter-relations can be more clearly understood through a critical appreciation of the fundamental opposition; a Pakeha imperative for cultural dominance: assimilation on the one hand, and a Maori imperative for cultural recognition: survival, on the other. Of significance are the ways in which the dialectic between these fundamental oppositions are mediated and transformed by Ngati Piritai as they live out their lives in a societal context of contested power relations.
Keywords: print only

Discourses and silences: indigenous peoples, risks and resistance - Cant, Garth; Goodall, Anake; Inns, Justine (Dept. of Geography, University of Canterbury, 2005)
Keywords: civil Rights; human rights; iwi taketake; print only; unsure if maori

The Treaty and the word: the colonization of Māori philosophy - Jackson, Moana (Justice, ethics and New Zealand society, 1992)
Keywords: environment; kaupapa māori; philosophy; print only; rangatiratanga; social justice; sovereignty; tiriti o waitangi/treaty of waitangi

Māori property rights and the foreshore and seabed: the last frontier - Charters, Claire; Erueti, Andrew (Victoria University Press, 2007)
"In this era of indigenous peoples' rights recognition, states around the globe are faced with reconciling the pre-existing, inherent rights of indigenous peoples with those held and asserted by the state. This fact was brought into sharp focus in New Zealand by the Court of Appeal decision of Ngati Apa." "This collection of essays does not aim to be an exhaustive treatment of the legal issues raised by Ngati Apa and the Foreshore and Seabed Act 2004 (the FSA). It does, however, address many of the most salient."--BOOK JACKET.
Keywords: iwi taketake; kaitiakitanga; law; legislation; new zealand foreshore and seabed act 2004; print only; seashore; shorelines; takutai moana; tikanga | indigenous law; treaty claims; ture whenua

Indigenous legal theory: some initial consideration - Benjamin J. Richardson; Charters, Claire (Indigenous peoples and the law: comparative and critical perspectives, 2009)
"Provides an historical, comparative and contextual analysis of various legal and policy issues affecting indigenous peoples. It focuses on the common law jurisdictions of Australia, Canada, New Zealand and the United States, as well as relevant international law developments"--Back cover.
Keywords: crown law; ethnic identity; international law; iwi taketake; law; print only; self-determination

Conversations about indigenous rights: the UN Declaration on the Rights of Indigenous Peoples and Aotearoa New Zealand - Katene, Selwyn; Taonui, Rawiri (Massey University Press, 2018)
The UN declaration on the Rights of Indigenous Peoples is a deeply significant document. In 2007, then UN Secretary-General Ban Ki-moon described its signing as an "historic moment when UN Member States and indigenous peoples reconciled with their painful histories and resolved to move forward together on the path of human rights, justice and development for all". This book reflects on the tenth anniversary of the UN General Assembly's adoption of the Declaration and examines its relevance in New Zealand. It shows the strong alignment between the Treaty of Waitangi and the Declaration, and examines how the Declaration assists the interpretation and application of Treaty principles of partnership, protection and participation. Starting from a range of viewpoints and disciplines, the authors agree that in Aotearoa New Zealand the journey to full implementation is now well underway, but warn that greater political leadership, willpower, resources and a stronger government commitment is needed.
Keywords: UNDRIP; civil Rights; international relations; print only; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi